Identifikasi dan Mitigasi Risiko Banjir Berulang di FMIPA Universitas Negeri Padang dalam Menunjang Keberlangsungan Aktivitas Akademik - Keysha Ardian Fatika; Mutya Ayu Henirwan; Nadila Desmiati; Nina Puspita; Tia Ayu Ningrum (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Recurrent flooding poses a tangible threat to the continuity of academic activities in higher education institutions located in disaster-prone areas. This study aims to identify the risks of recurrent flooding at the Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, and to formulate effective mitigation strategies to ensure the continuity of learning activities. The research adopts a qualitative approach with a case study design. Data were collected through in-depth interviews with lecturers, administrative staff, and students, as well as field observations and documentation studies of historical flood events and institutional policies. Data analysis was conducted thematically to identify risk patterns and mitigation strategies. The findings indicate that flood risks at FMIPA UNP originate from geographical factors, inadequate drainage infrastructure, and changes in land use surrounding the campus. The impacts of flooding include disruptions to academic activities, damage to laboratory facilities, and restricted access for students and lecturers. Risk analysis using the Estimated Maximum Loss (EML) approach reveals that laboratory damage and disruptions to lecture schedules represent the highest risk levels. Recommended mitigation efforts include improving drainage systems, constructing protective embankments, establishing evacuation routes, and developing adaptive online-based learning systems as contingency measures. Recovery strategies focus on strengthening institutional capacity through disaster preparedness training, the establishment of emergency response teams, and enhanced collaboration with local governments and the National Disaster Management Agency (BNPB). This study underscores the importance of integrated disaster risk management in higher education governance to ensure educational resilience and sustainability.